Fiscal reaction functions across the world : a battle of statistical (in-) significance - Afonso, António (2018)
We estimate fiscal reaction functions for a panel of 173 countries using data between 1970-2014. Most notably, we assess the existence of non-Ricardian regimes, as postulated in the Fiscal Theory of the Price Level (FTPL), or, contrarily, the possibility of Ricardian regimes. By means of several, well established and state-of-the-art, panel data techniques, we find that: governments have on average increased the primary balance as a response to higher previous government indebtedness, implying a Ricardian fiscal regime, contradicting the FTPL. In addition, the Ricardian results are confirmed for the advanced countries and for the euro area group, but are less clear for the other country groups, lacking statistical significance. A more Ricardian fiscal regime emerged essentially after 1995 and notably in the sub-period 2008-2014, after the Global Financial Crisis (before that statistical insignificance is the norm) From a P-VAR analysis, we find that increases in government indebtedness increase primary balances, supporting overall the existence of an average Ricardian fiscal regime.